Mapping the Magnetic Anisotropy at the Atomic Scale in Dysprosium Single‐Molecule Magnets - Klahn, Emil A.; Gao, Chen; Gillon, Beatrice; Gukasov, Arsen; Fabrèges, Xavier; Piltz, Ross O.; Jiang, Shang‐Da; Overgaard, Jacob (Chemistry : a European journal, 2018)
The anisotropy of the magnetic properties of molecular magnets is a key descriptor in the search for improved magnets. Herein, it is shown how an analytical approach using single‐crystal polarized neutron diffraction (PND) provides direct access to atomic magnetic susceptibility tensors. The technique was applied for the first time to two Dy‐based single‐molecule magnets and showed clear axial atomic susceptibility for both DyIII ions. For the triclinic system, bulk magnetization methods are not symmetry‐restricted, and the experimental magnetic easy axes from both PND, angular‐resolved magnetometry (ARM), and theoretical approaches all match reasonably well. ARM curves simulated from the molecular susceptibility tensor determined with PND show strong resemblance with the experimental ones. For the monoclinic compound, comparison can only be made with the theoretically calculated magnetic anisotropy, and in this case PND yields an easy‐axis direction that matches that predicted by electrostatic methods. Importantly, this technique allows the determination of all elements of the magnetic susceptibility tensor and not just the easy‐axis direction, as is available from electrostatic predictions. Furthermore, it has the capacity to provide each of the anisotropic magnetic susceptibility tensors for all independent magnetic ions in a molecule and thus allows studies on polynuclear complexes and compounds of higher crystalline symmetry than triclinic. Beating symmetry: Experimental determination of the magnetic anisotropy of individual molecules in a crystal of symmetry higher than triclinic is a long‐standing challenge in molecular magnetism. Polarized neutron diffraction separates individual ionic contributions to the unit‐cell susceptibility and thus provides a powerful tool to compare theoretical and experimental results, which is applicable to all molecular and crystalline symmetries.